A Celestial Omnibus : Short Fiction on Faith - Maney, J. P. (Jonathan Paul), 1956-; Hazuka, Tom. (Boston : Beacon Press, 1997)
Twenty-fives stories on faith. In Little Miracles, Kept Promises by Sandra Cisneros, a Latino community's hopes in Texas are revealed in letters to the saints, in A Father's Story by Andre Dubus, a man covers up a deadly hit-and-run to save his daughter from jail, and Isaac Bashevis Singer's Gimpel the Fool is on a village cuckold.
Mystery. Little miracles, kept promises / Sandra Cisneros ; A father's story / Andre Dubus ; Christmas / Vladimir Nabokov ; Mr. Green ; Robert Olen Butler ; The man to send / Leslie Marmon Silko ; Rain clouds / Leslie Marmon Silko -- Doubt. The expert on God / John L'Heureux ; The conversion of the Jews / Philip Roth ; Pigeon feathers / John Updike ; Watching her die / Reynolds Price ; All stories are true / John Edgar Wideman -- Evil. Obasan / Joy Kogawa ; Sweat / Zora Neale Hurston ; God's world / Najib Mahfuz ; Good contry people / Flannery O'Connor ; Act of faith / Irwin Shaw -- The supernatural. Love medicine / Louise Erdrich ; The celestial omnibus / E.M. Forster ; On mortality / Maxine Hong Kingston ; The silver crown / Bernard Malamud ; The man in the black suit / Stephen King -- Reconciliation. Cathedral / Raymond Carver ; Zoo animal keeper 1, REC-SVC-ZK / Martha Gies ; First confession / Frank O'Connor ; Gimpel the fool / Isaac Bashevis Singer ; Everyday use / Alice Walker.
Includes index.
Also issued online.
Keywords: American fiction -- 20th century; Faith -- Fiction; Short stories, American; Geloof